Utilization and out-of-pocket expenses of primary care among the multimorbid elderly in China: A two-part model with nationally representative data - Chen, Yuehua; Liu, Wenbin (Frontiers in Public Health, 2022)
Background: Multimorbidity has become an essential public health issue that threatens human health and leads to an increased disease burden. Primary care is the prevention and management of multimorbidity by providing continuous, comprehensive patient-centered services. Therefore, the study aimed to investigate the determinants of primary care utilization and out-of-pocket expenses (OOPE) among multimorbid elderly to promote rational utilization of primary care and reduce avoidable economic burdens. Methods: The study used data from CHARLS 2015 and 2018, which included a total of 4384 multimorbid elderly aged 60 and above. Guided by Grossman theory, determinants such as education, gender, marriage, household economy, and so on were included in this study. A two-part model was applied to evaluate primary care utilization and OOPE intensity in multimorbid populations. And the robustness testing was performed to verify research results. Results: Primary care visits rate and OOPE indicated a decline from 2015 to 2018. Concerning primary outpatient care, the elderly who were female(OR=1.51,P<0.001), married (OR=1.24,P<0.05), living in rural areas(OR=1.77,P<0.001) and with poor self-rated health(OR=2.23,P<0.001) had a significantly higher probability of outpatient utilization, whereas those with middle school education(OR=0.61,P<0.001) and better household economy(OR=0.96,P<0.001) had a significantly less likelihood of using outpatient care. Rural patients(β=-0.72,P<0.05) may have lower OOPE, while those with better household economy (β=0.29,P<0.05;β=0.58,P<0.05) and poor self-rated health(β=0.62,P<0.001) occurred higher OOPE. Regarding primary inpatient care, adults who were living in rural areas(OR=1.48,P<0.001), covered by Urban Employee Basic Medical Insurance(UEBMI) or Urban Rural Basic Medical Insurance(URBMI)(OR=2.46,P<0.001;OR=1.81,P<0.001) and with poor self-rated health (OR=2.30,P<0.001) had a significantly higher probability of using inpatient care, whereas individuals who were female(OR=0.74,P<0.001), with middle school education(OR=0.40,P<0.001) and better household economy(OR=0.04,P<0.001) had a significantly lower tendency to use inpatient care. Significantly, more OOPE occurred by individuals who were women(β=0.18,P<0.05) and with better household economy (β=0.40,P<0.001;β=0.62,P<0.001), whereas those who were covered by URBMI(β=-0.25,P<0.05)and satisfied with their health(β=-0.21,P<0.05) had less OOPE. Conclusion: To prompt primary care visits and reduce economic burden among subgroups, more policy support is in need, such as tilting professional medical staff and funding to rural areas, enhancing awareness of disease prevention among vulnerable groups and so on.